Empowerment of Yasinan Group in the Control of Non-Communicable Diseases Through Nursing Case Based on Complementary Therapy - Rozhabbi Dwi Cahyono; Erni Setiyorini; Raden Roro Dewi Rahmawaty Aktyani Putri (STIKes Patria Husada Blitar, 2025)
Non-communicable diseases (NCDs) such as hypertension, diabetes, cholesterol, and uric acid are the leading causes of morbidity and mortality in Indonesia, especially among elderly populations in rural areas. Lack of knowledge, limited access to healthcare services, and poor early detection exacerbate this situation. This community service program aimed to implement the empowerment of the Yasinan Group (Qur’an Recitation Group) in controlling non-communicable diseases through nursing care based on complementary therapy. The program was carried out among a men’s Yasinan group in RT 01 RW 02, Tlogo Village, Kanigoro District, Blitar, involving 35 participants. The method consisted of assessment, diagnosis, intervention, implementation, and evaluation. Interventions included health education, free health check-ups, and acupressure therapy training. The interventions include health education, free health check-ups, and the promotion of acupressure techniques based on the standard operating procedure (SOP) for acupressure. These interventions were delivered over three meetings and involved measuring blood pressure, blood sugar, uric acid, and cholesterol, alongside acupressure therapy. Results showed a reduction in uric acid levels among participants with elevated levels by 1–1.2 mg/dL, The prevalence of hypertension decreased from 17 participants to 10, and blood sugar levels normalized in all participants. There was also an increase in participants’ knowledge and awareness of NCDs. Education-based interventions, routine health checks, and acupressure therapy were effective in reducing NCD risk and promoting healthy living behaviors. This model has potential for wider application as a community empowerment strategy in controlling NCDs.